2014
DOI: 10.1371/journal.pone.0112786
|View full text |Cite|
|
Sign up to set email alerts
|

Whole Blood Transcriptional Profiling Reveals Deregulation of Oxidative and Antioxidative Defence Genes in Myelofibrosis and Related Neoplasms. Potential Implications of Downregulation of Nrf2 for Genomic Instability and Disease Progression

Abstract: The Philadelphia-negative chronic myeloproliferative neoplasms - essential thrombocythemia (ET), polycythemia vera (PV), and myelofibrosis (MF) (MPNs) - have recently been shown to be associated with chronic inflammation, oxidative stress and accumulation of reactive oxygen species (ROS). Using whole blood transcriptional profiling, we report that several oxidative stress and anti-oxidative stress genes are significantly deregulated in MPNs. Among the twenty most up- and downregulated genes, ATOX1, DEFB122, GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 53 publications
5
79
0
1
Order By: Relevance
“…In this regard, we have also by transcriptional profiling studies described a marked deregulation of oxidative and antioxidative stress genes [112], supporting the concept of chronic inflammation as the driving force for clonal evolution in MPNs. Most recently, our mathematical modeling studies have also delivered the proof of concept for MPNs as a human inflammation model for cancer development [113].…”
Section: Mechanisms Of Action Of Ifn-alpha2supporting
confidence: 61%
“…In this regard, we have also by transcriptional profiling studies described a marked deregulation of oxidative and antioxidative stress genes [112], supporting the concept of chronic inflammation as the driving force for clonal evolution in MPNs. Most recently, our mathematical modeling studies have also delivered the proof of concept for MPNs as a human inflammation model for cancer development [113].…”
Section: Mechanisms Of Action Of Ifn-alpha2supporting
confidence: 61%
“…In this regard, an analysis of the antioxidant defense pathway-gene expression array using RNA from wild type and NRF2-null mice tissue, revealed that the expression of GPX8 was down-regulated in the absence of NRF2 [60]. In line with this, transcriptome analysis from patient samples suffering from myeloproliferative neoplasms, polycythemia or myelofibrosis, diseases also associate with oxidative stress and low-grade chronic inflammation, show lower expression levels of both NRF2 and GPX8 compared with control subjects [61]. There are not yet studies that specifically involve GPX8 in human brain protection but a transcriptome analysis in mice indicates a compensatory GPX8 increase in response to the Parkinsonian toxin MPTP [62].…”
Section: Nrf2 Participates In the Unfolded Protein Response (Upr)mentioning
confidence: 69%
“…The egress of CD34+ cells from the stem cell niches into the circulation has been compared to the metastatic process in solid tumors [49], in which a large number of chemokines, cytokines and proteolytic enzymes are deeply involved [2326, 5053]. In this process–as well as in the progression of myelofibrosis from early cancer stage to the advanced cancer stage (MMM)–inflammation and immune deregulation is today considered of major importance [2123, 5357].…”
Section: Discussionmentioning
confidence: 99%